Resolução de problemas de minimização com uso do cálculo variacional - Matos, Lucas de Sousa (Universidade Federal do Tocantins, 2023)
The present work aims to present some applications, in everyday problems, of the minimi- zation problem using variational calculus. For this purpose, we did a purely bibliographic